ANALISIS PERLAKUAN AKUNTANSI TRANSAKSI ASURANSI SYARIAH TERHADAP PSAK 108 PADA PT BUMIPUTERA MUDA SYARIAH CABANG SERANG - Hendrieta Hendrieta; Virlia Virlia (UIN Sultan Maulana Hasanuddin Banten, 2020)
The accounting records regarding sharia insurance transactions with PSAK 108 have the objective to produce accurate, reliable and relevant financial reports. With the existence of financial statements in accordance with applicable accounting standards, the financial statements are expected to make the reference for the public to be confident and increasingly feel secure with the Islamic insurance company. Based on the background above, the formulation of the problem in this study are: How is the application of PSAK No.108 on accounting treatment of sharia insurance at PT. Bumiputera Muda Syariah Serang Branch. The purpose of this study is to determine whether the accounting treatment of sharia insurance transactions is in accordance with PSAK 108 or not. Based on what is used in this study is a qualitative method. The data used are primary data and secondary data. Primary data is conducting interviews and direct observation at PT. Bumiputera Muda 1967 Serang Branch. Secondary data in the form of sources from books, websites, articles, relevant previous research studies and other sources. The results showed that Islamic Insurance PT. Bumiputera Muda 1967 has not fully implemented PSAK 108. Evidenced by the financial statements made, there is still a discrepancy with PSAK 108. This is due to the policies in the company's management in preparing financial statements in each of its subsidiary companies. This is caused by the system of recording financial statements in branch offices in a computerized and recapitalized data directly by the center.